2014
DOI: 10.3171/2014.7.jns131990
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in soluble epoxide hydrolase: association with outcome after aneurysmal subarachnoid hemorrhage

Abstract: Object Patients with aneurysmal subarachnoid hemorrhage (SAH) are at high risk for delayed cerebral ischemia (DCI) and stroke. Epoxyeicosatrienoic acids (EETs) play an important role in cerebral blood flow regulation and neuroprotection after brain injury. Polymorphisms in the gene for the enzyme soluble epoxide hydrolase (sEH), which inactivates EETs, are associated with ischemic stroke risk and neuronal survival after ischemia. In this prospective observational study of patients with SAH we compare vital and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Thus it is likely that the benefits of sEH deletion are multifactorial. Overall, these findings complement our previous work demonstrating improved outcomes after SAH in both humans 17 and mice 16 when sEH activity is altered, and support the hypothesis that sEH inhibition may be a viable therapeutic strategy in SAH.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus it is likely that the benefits of sEH deletion are multifactorial. Overall, these findings complement our previous work demonstrating improved outcomes after SAH in both humans 17 and mice 16 when sEH activity is altered, and support the hypothesis that sEH inhibition may be a viable therapeutic strategy in SAH.…”
Section: Discussionsupporting
confidence: 87%
“…We have previously demonstrated that mice with elevated levels of EETs due to genetic deletion of their metabolizing enzyme soluble epoxide hydrolase (sEH knockout, sEHKO mice) are protected from experimental cerebral ischemia 15 and delayed microvascular dysfunction 16 after experimental SAH. Further, we have shown that patients with genetic polymorphisms that reduce sEH activity have improved outcomes after SAH 17 . We hypothesized that the beneficial effects of EETs also modulate acute inflammation and edema formation after SAH.…”
Section: Introductionmentioning
confidence: 88%
“…Various studies have shown that EETs protect the brain during stroke and that inhibition of sEH enhances this effect (10). Patients suffering aneurysmal subarachnoid hemorrhage are at high risk for delayed cerebral ischemia and stroke (11). Patients with the common K55R genetic polymorphism in the sEH gene ( Ephx2 ) demonstrated 30% lower levels of EETs due to increased activity of sEH (12) and they exhibited a mortality of 28.6% after stroke versus 5.3% in the control subjects (11).…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that in patients admitted with aneurysmal SAH (aSAH), those with the Lys55Arg (K55R) polymorphism, predictive of increased sEH activity, had a significantly increased likelihood of experiencing a new stroke compared to patients with the wild-type gene. No difference was observed between patients with Arg287Gln (R287Q), associated with decreased EET metabolism and increased EETs, or wild-type genotypes (Martini et al, 2014); the same pattern was also observed for mortality. However, despite the increased likelihood of stroke in the K55R group, neurological deterioration attributable to DCI is not changed by genotype, though patients with the R287Q polymorphism had a significantly reduced length of hospital stay compared to either K55R or wild-type (Martini et al, 2014).…”
Section: Cerebrovascular Pathology and Cytochrome P450 Eicosanoidsmentioning
confidence: 74%
“…No difference was observed between patients with Arg287Gln (R287Q), associated with decreased EET metabolism and increased EETs, or wild-type genotypes (Martini et al, 2014); the same pattern was also observed for mortality. However, despite the increased likelihood of stroke in the K55R group, neurological deterioration attributable to DCI is not changed by genotype, though patients with the R287Q polymorphism had a significantly reduced length of hospital stay compared to either K55R or wild-type (Martini et al, 2014). Sampling CSF after aSAH showed that CYP2C8*4 allele carriers had decreased EETs and DHETs CSF levels, and were over twice as likely to develop DCI and clinical neurologic deterioration, the latter defined in this study as a decrease of two points on the Glasgow Outcome Scale.…”
Section: Cerebrovascular Pathology and Cytochrome P450 Eicosanoidsmentioning
confidence: 74%